Private Extensionists’ Role in an Effort to Achieve SDGs through Peri-Urban Community Empowerment - Sumardjo; Adi Firmansyah; Leonard Dharmawan (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
Infrastructure development has forced the transformation of rural farming communities to peri-urban communities and impacted community unreadiness. In Presidential Decree No. 59/2017, the Sustainable Development Goals (SDGs) have been set as indicators of Indonesia's development. Private extensionists have a fundamental role in community empowerment as the implementation of Corporate Social Responsibility (CSR) in large companies. This research has built an alternative concept of private extensionists in the SDGs. The research objectives are to analyze the role of private extensionists in community empowerment through self-social engineering and to analyze the impact of community empowerment on the SDGs' achievement. The research method used is participatory action research supported by a cybernetic approach: participant-observer, triangulation techniques, and focus group discussion (FGD). The results showed that private extensionists' implementing the concept of self-social engineering effectively empowered the community. This effectiveness occurs by placing the community as the subject of creative social energy in empowerment. This is in line with the application of the participatory communication paradigm and dialogue, which causes a communication convergence between participants. The peri-urban community empowerment approach in organic farming development positively impacts the achievement of SDGs.